Eliminating human rabies deaths: rabies as a disease and a global burden - Cleaveland, OBE, FRS, Sarah (Henry Stewart Talks, 2020)
Rabies, Host species of rabies, Global burden of canine rabies, Prevention of rabies with mass vaccination, Post-Exposure Prophylaxis (PEP), One Health approach